Threshold-Dependent Gene Drives in the Wild: Spread, Controllability, and Ecological Uncertainty. (18th September 2019) - Backus, Gregory A; Delborne, Jason A
Abstract: Gene drive technology could allow the intentional spread of a desired gene throughout an entire wild population in relatively few generations. However, there are major concerns that gene drives could either fail to spread or spread without restraint beyond the targeted population. One potential solution is to use more localized threshold-dependent drives, which only spread when they are released in a population above a critical frequency. However, under certain conditions, small changes in gene drive fitness could lead to divergent outcomes in spreading behavior. In the face of ecological uncertainty, the inability to estimate gene drive fitness in a real-world context could prove problematic because gene drives designed to be localized could spread to fixation in neighboring populations if ecological conditions unexpectedly favor the gene drive. This perspective offers guidance to developers and managers because navigating gene drive spread and controllability could be risky without detailed knowledge of ecological contexts.